A comparative study of myocardial function and morphology during fasting/refeeding and food restriction in rats - Pinotti, Matheus Fécchio [UNESP]; Leopoldo, André Soares [UNESP]; Silva, Maeli Dal-Pai [UNESP]; Sugizaki, Mário Mateus [UNESP]; Do Nascimento, André Ferreira [UNESP]; Lima-Leopoldo, Ana Paula [UNESP]; Aragon, Flávio Ferrari [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Elsevier, 2010)
Background: This study compared the influence of fasting/refeeding cycles and food restriction on rat myocardial performance and morphology. Methods: Sixty-day-old male Wistar rats were submitted to food ad libitum (C), 50% food restriction (R50), and fasting/refeeding cycles (RF) for 12 weeks. Myocardial function was evaluated under baseline conditions and after progressive increase in calcium and isoproterenol. Myocardium ultrastructure was examined in the papillary muscle. Results: Fasting/refeeding cycles maintained rat body weight and left ventricle weight between control and food-restricted rats. Under baseline conditions, the time to peak tension (TPT) was more prolonged in R50 than in RF and C rats. Furthermore, the maximum tension decline rate (-dT/dt) increased less in R50 than in RF with calcium elevation. While the R50 group showed focal changes in many muscle fibers, such as the disorganization or loss of myofilaments, polymorphic mitochondria with disrupted cristae, and irregular appearance or infolding of the plasma membrane, the RF rats displayed few alterations such as loss or disorganization of myofibrils. Conclusion: Food restriction promotes myocardial dysfunction, not observed in RF rats, and higher morphological damage than with fasting/refeeding. The increase in TPT may be attributed possibly to the disorganization and loss of myofibrils; however, the mechanisms responsible for the alteration in -dT/dt in R50 needs to be further clarified. © 2010 Elsevier Inc. All rights reserved.
Keywords: Fasting; Food restriction; Inotropic stimulation; Myocardial function; Refeeding; Ultrastructure morphology; calcium; isoprenaline; animal cell; animal experiment; animal tissue; body weight; cell membrane; controlled study; diet restriction; heart function; heart left ventricle; heart muscle; male; mitochondrion; morphology; muscle cell; muscle fibril; muscle function; myofilament; nonhuman; priority journal; rat; refeeding; ultrastructure; Animals; Electrophysiology; Food Deprivation; Male; Microscopy, Electron, Transmission; Muscle Contraction; Papillary Muscles; Rats; Rats, Wistar